Patterns of compartment involvement in tibiofemoral osteoarthritis in men and women and in whites and African Americans - Wise, Barton L.; Niu, Jingbo; Yang, Mei; Lane, Nancy E.; Harvey, William; Felson, David T.; Hietpas, Jean; Nevitt, Michael; Sharma, Leena; Torner, Jim; Lewis, C. E.; Zhang, Yuqing (Arthritis care & research (2010), 2012)
Objective We conducted a cross‐sectional study to describe the prevalence of tibiofemoral joint space narrowing (JSN) in medial and lateral compartments and assess whether it differs by sex and ethnic groups, and, if it does, to what extent such a difference is accounted for by knee malalignment. Methods The Multicenter Osteoarthritis Study is an observational study of persons ages 50–79 years with either symptomatic knee osteoarthritis or high risk of disease. Knee radiographs were assessed for JSN in each tibiofemoral compartment. Mechanical axis angle was measured using full‐extremity films. We compared the proportion of knees with medial compartment JSN and with lateral JSN between men and women, as well as between whites and African Americans, using a logistic regression model adjusting for covariates (race or sex and body mass index, age, education, and clinic site). We used generalized estimating equations to account for correlation between 2 knees within a person. Results Of 5,202 knees (2,652 subjects), 1,532 (29.5%) had medial JSN and 427 (8.2%) had lateral JSN. Lateral JSN was more prevalent in the knees of women than in men (odds ratio [OR] 1.9, 95% confidence interval [95% CI] 1.5–2.4) and was also higher in the knees of African Americans than in whites (OR 2.4, 95% CI 1.7–3.3). Further adjustment for malalignment attenuated the OR for sex but not the OR for race. Conclusion Women and African Americans are more likely to have lateral JSN than men and whites, respectively. Valgus malalignment may contribute to the higher prevalence in women.